MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN MEMBACA PEMAHAMAN MENGGUNAKAN KOMBINASI MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC), TALKING STICK DAN COURSE REVIEW HORAY PADA MATA PELAJARAN BAHASA INDONESIA KELAS V SDN PASAR LAMA 3 BANJARM - Safitri, Assyifa Nuryana; Sari, Dessy Dwitalia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study highlights the low level of reading comprehension and critical thinking skills among students in Indonesian due to their inability to understand text content, solve problems, and make decisions. The solution proposed is to implement a combination of the Cooperative Integrated Reading and Composition, Talking Stick, and Course Review Horay learning models to improve students' critical thinking and reading comprehension skills. Through a qualitative approach using Classroom Action Research (CAR) and four sessions at SDN Pasar Lama 3 Banjarmasin, the research results showed a significant improvement in students' critical thinking skills from 10% to 90% and reading comprehension from 10% to 95%. In conclusion, the combination of learning models applied can enhance students' critical thinking skills and collaboration in Indonesian language learning.